1997
DOI: 10.1046/j.1464-410x.1997.00426.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of enuresis and other bladder symptoms in patients with active Graves’ disease

Abstract: Objective  To determine the prevalence of bladder symptoms in patients with Graves’ disease and assess their abnormalities on urodynamic studies. Patients and methods  The study comprised 30 consecutive patients (13 female, 17 male, mean age 31 years, sd 10) with active Graves’ disease. Before and after attaining euthyroidism with carbimazole, their bladder symptoms were assessed using a questionnaire adapted from the American Urologic Association voiding symptom score, the serum levels of total triiodo‐l‐thyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 1 publication
1
15
0
2
Order By: Relevance
“…This study indicates an increased prevalence of LUTS among women with RA when compared with the healthy control population, and the current data is in accordance with the previous studies that report increased prevalence of LUTS among individuals with other autoimmune diseases (4)(5)(6)(7)(8). The presence of LUTS is associated with lower QoL in affected individuals.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This study indicates an increased prevalence of LUTS among women with RA when compared with the healthy control population, and the current data is in accordance with the previous studies that report increased prevalence of LUTS among individuals with other autoimmune diseases (4)(5)(6)(7)(8). The presence of LUTS is associated with lower QoL in affected individuals.…”
Section: Discussionsupporting
confidence: 91%
“…Micturition pathophysiology has not been clearly defined in these autoimmune diseases; however, autoantibody mediated autonomic nerve pathway of the bladder is believed to play an important role in this process (4,8,9). Peeker et al (15) have reported there was interstitial cystitis (IS) in 13% of the patients with RA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In an earlier study, we have described dyssynergia of the detrusor muscle as the cause of urinary bladder dysfunction in patients with thyrotoxicosis, which reversed on treatment (8). It is possible that dyssynergia of the thoracic diaphragm muscle might have contributed to poor diaphragmatic muscle pressure and its movement during deep respiration.…”
Section: Discussionmentioning
confidence: 97%